2018
DOI: 10.3390/ijerph15102138
|View full text |Cite
|
Sign up to set email alerts
|

How and When Are Job Crafters Engaged at Work?

Abstract: The importance of work engagement and the lack of engaged employees have led researchers to focus on how to enhance employees’ levels of engagement in the workplace. Although job crafting as a principal driver of work engagement has recently received much attention from academics, little is known about the processes and conditions in which employees who craft their tasks become engaged. In order to address these research gaps, we hypothesize that psychological capital (PsyCap) is likely to mediate the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
(107 reference statements)
0
14
0
Order By: Relevance
“…This means that subordinates' PsyCap may play a mediating role in the relationship between leader humility and subordinates' OCB/withdrawal behavior. First, several previous studies support the promoting effect of positive PsyCap on employees' extra-role behaviors [10,41,42,[46][47][48]. For example, Qian et al [46] found that employees with higher self-efficacy are less reluctant to speak up; Norman et al's [10] research demonstrated that positive PsyCap can promote employees to engage in more OCB and fewer deviance behaviors; and Avey et al's [48] meta-analysis supported the idea that PsyCap is positively related to desirable OCB behaviors, and negatively related to undesirable behaviors (turnover and deviance).…”
Section: The Mediating Role Of Subordinates' Psycapmentioning
confidence: 81%
See 2 more Smart Citations
“…This means that subordinates' PsyCap may play a mediating role in the relationship between leader humility and subordinates' OCB/withdrawal behavior. First, several previous studies support the promoting effect of positive PsyCap on employees' extra-role behaviors [10,41,42,[46][47][48]. For example, Qian et al [46] found that employees with higher self-efficacy are less reluctant to speak up; Norman et al's [10] research demonstrated that positive PsyCap can promote employees to engage in more OCB and fewer deviance behaviors; and Avey et al's [48] meta-analysis supported the idea that PsyCap is positively related to desirable OCB behaviors, and negatively related to undesirable behaviors (turnover and deviance).…”
Section: The Mediating Role Of Subordinates' Psycapmentioning
confidence: 81%
“…Very simply, PsyCap can be viewed as "who you are" and "what you can become in terms of positive development" [39] and is differentiated from human capital ("what you know"), social capital ("who you know"), and financial capital ("what you have") [1]. Some studies have confirmed that individual PsyCap has positive effects on individuals' job attitudes [40,41], work behaviors [42], and performance [1,40]. In addition, PsyCap has been shown to predict satisfaction with work, health, relationships, and life in general [43,44].…”
Section: Leader Humility and Subordinates' Psycapmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, individuals can perform behaviors through job crafting to balance the relationship between demands and resources at work. Job crafting is a set of initiatives of change generated by the person to make the job better fit their expectations and needs [9]. In this sense, Bakker and Demerouti [10] added that it is an individual and proactive action aimed at changing the job to make it more "engaging" and less tiring.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also highlighted that job crafting is an antecedent of work engagement in general (Shin et al 2018), although this relationship has not been explored in the trade union field. Labor union activity is voluntary and, therefore, seems closely related to job crafting.…”
Section: Introductionmentioning
confidence: 99%